Determination of Heavy Metals Concentration in Vegetables Irrigated with Water from Industrial Streams in Kano State. - M. A , Olayiwola; Emmanuel , Bernard (African Journal of Education,Science and Technology (AJEST), 2016)
Consumption of vegetables is on the increase world-wide as a result of its health benefits. Consequently, the demand for vegetables keeps increasing while the easiest means of vegetable cultivation especially in urban centers is by irrigation. Proliferation of vegetable gardens along industrial streams in Kano metropolis prompted this study aimed at determining the concentration of heavy metals in vegetables grown with such water body and ascertains their suitability for human consumption. Against this background objective, concentrations of (Fe, Cr, Ni, Cu and Zn) were determined in onions, tomato and carrot grown in these areas. Samples were collected for eight months; Atomic absorption spectrometry was used to determine the concentrations and t-test to analyze the metals in the vegetables. The mean and standard deviation concentration for each heavy metal in the samples was determined. Findings indicated the value (mg/kg) for onions 507.87 ± 12.80, Fe; 4.97± 0.00, Cr; 3.28 ± 1.08, Ni; 8.73 ± 0.81, Cu and 336.50 ± 242.83, Zn. Carrot had 402.93 ± 40.93, Fe; 5.95 ± 0.01, Cr; 6.65 ± 0.98, Ni; 22.50 ± 3.17, Cu and 220.00 ± 67.33, Zn .The values for tomato were; 431.80 ± 111.80, Fe; 5.72 ± 0.38, Cr; 2.73 ± 0.13, Ni; 15.40 ± 0.80, Cu and 72.83 ± 24.50 mg/kg, Zn. With the exception of Ni and Cu and for Fe in Carrot and Zn in tomato other values were higher than the permissible levels set by the Food and Agriculture Organization (FAO) and World Health Organization (WHO). Invariably, it is obvious that vegetables grown in this region may pose health hazard if consumed. The Ministries of Health and Environment should wade in, provide possible treatment for effluents or discourage vegetable farming along these streams or provide alternative locations for them.